2008
DOI: 10.1371/journal.pgen.1000242
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Analysis of PRC1 and PRC2 Occupancy Identifies Two Classes of Bivalent Domains

Abstract: In embryonic stem (ES) cells, bivalent chromatin domains with overlapping repressive (H3 lysine 27 tri-methylation) and activating (H3 lysine 4 tri-methylation) histone modifications mark the promoters of more than 2,000 genes. To gain insight into the structure and function of bivalent domains, we mapped key histone modifications and subunits of Polycomb-repressive complexes 1 and 2 (PRC1 and PRC2) genomewide in human and mouse ES cells by chromatin immunoprecipitation, followed by ultra high-throughput seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
1,011
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 905 publications
(1,077 citation statements)
references
References 66 publications
59
1,011
3
4
Order By: Relevance
“…Polycomb-like proteins (PCLs), including PHF1, MTF2 and PHF19, are PRC2 associated factors that form sub-complexes with PRC2 core components 3 , and have been proposed to modulate PRC2’s enzymatic activity or its recruitment to specific genomic loci 413 . Mammalian PRC2 binding sites are enriched in CG content, which correlate with CpG islands that display a low level of DNA methylation 14 . However, the mechanism of PRC2 recruitment to CpG islands is not fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polycomb-like proteins (PCLs), including PHF1, MTF2 and PHF19, are PRC2 associated factors that form sub-complexes with PRC2 core components 3 , and have been proposed to modulate PRC2’s enzymatic activity or its recruitment to specific genomic loci 413 . Mammalian PRC2 binding sites are enriched in CG content, which correlate with CpG islands that display a low level of DNA methylation 14 . However, the mechanism of PRC2 recruitment to CpG islands is not fully understood.…”
mentioning
confidence: 99%
“…3f, g, h). PRC2 and its associated PCL proteins are commonly located at CpG islands 14 . Our finding that PCL proteins specifically recognize unmethylated CpG-motifs through their EH WH domains provides a direct link between CpG islands and PRC2 recruitment.…”
mentioning
confidence: 99%
“…PRC2 might also associate with CG-rich sequences in genes devoid of DNA motifs for transcriptional activators in ES cells. 50 We found that SUZ12 and EZH2 interact with Spi-1 and bind to the Bim promoter at the H3K27me3 sites that are 0.9 kb distant from the Spi-1 binding motif. As both Spi-1 and PRC2 are required to favour H3K27m3 at the Bim promoter, at least, two scenarios might fit with these findings (Figure 7f).…”
Section: α-Suz12mentioning
confidence: 72%
“…In addition, some enzymes, e.g. MLL1, KDM2A, PRC2 have higher binding affinity at some DNA sequence elements, e.g., CpG islands (38)(39)(40)(41). To reflect these observations, we follow the treatment of Angel et al (10), and Hodge and Crabtree (11), to denote a "nucleation region" for a small number of nucleosomes, on which the enzymes have higher binding affinity compared to the nonspecific background binding affinity on other nucleosomes.…”
Section: Insert Figurementioning
confidence: 99%